Frugal Living dalam Perspektif Akuntansi : Pendekatan Systematic Literature Review - Putri, Trias Rachma; Yuhertiana, Indrawati (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to map the development of research on frugal living, green financial behavior, and financial resilience through a systematic literature review (SLR) and bibliometric analysis. The study was conducted using article data obtained from Google Scholar with the assistance of the Publish or Perish and VOSviewer software. Of the 300 initial articles identified, 21 articles published between 2021 and 2026 met the inclusion criteria and were analyzed in this study. The results indicate that frugal living not only represents thrifty behavior but also reflects behavioral accounting practices through financial planning, control, and evaluation activities at the individual level. The findings reveal a consistent pattern of relationships, wherein frugal living fosters the development of green financial behavior, which in turn contributes to enhanced financial resilience. Financial literacy, environmental awareness, and institutional support were identified as factors strengthening these relationships. The contribution of this research lies in expanding the behavioral accounting perspective from an organizational context to a personal financial management context by introducing the concept of personal management accounting. This concept explains that frugal living practices represent management accounting functions such as budgeting, cost control, and variance analysis, which support individual financial sustainability and strengthen long-term financial resilience.